THE ROLE OF ORGANIZATIONAL LEARNING AND MOTIVATION ROLE TO EMPLOYEE SATISFACTION - Yulius, Yosandi (Dinasti Publisher, 2022)
The purpose of this study was to determine and analyze: (1) Organizational Learning; (2) Work Motivation; (3) Job Satisfaction and (4) The Effect of Organizational Learning and Work Motivation on Employee Job Satisfaction at the Head Office of PT Sumber Alfaria Trijaya. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the employees at the Head Office of PT Sumber Alfaria Trijaya a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the organizational learning of employees at the PT Sumber Alfaria Trijaya Head Office was generally good and the work motivation of employees at the PT Sumber Alfaria Trijaya Head Office was generally good. Organizational Learning and Work Motivation have an effect on Employee Job Satisfaction at the Head Office of PT Sumber Alfaria Trijaya. Work motivation affects job satisfaction dominantly, so the Head Office of PT Sumber Alfaria Trijaya must maintain this condition so that job satisfaction for employees at the Head Office of PT Sumber Alfaria Trijaya remains consistent.